The Complete Illustrated Encyclopedia Of Horses & Ponies - Gorrie(3, (BSarahs; Catherine Austen; Nicola Jane Swinney; Pippa Roome (Beijing Flame Tree Publishing, 2008)
Written and compiled by experts and horse lovers, this comprehensive new encyclopedia covers everything you could want to know about these magnificent creatures. With 1,000 pictures-including anatomical illustrations- showing vital details, techniques and every breed, this is an indispensable horse reference, for anything from grooming to dealing with lameness, from Highland Pony to the Latvian Harness Horse
Keywords: Horses -- Ponies; Horses